SENTENCE PATTERNS OF NARRATIVE TEXT ENGLISH TEXTBOOK IN INDONESIA - Jaya, Aswadi (English Education Study Program Universitas Muhammadiyah Palembang, 2017)
A language may change its type over time as has happened with English which in the old English period was a synthetic language with many inflections and now is a rather analytic language with few grammatical endings that needs to be known and investigated. This study was aimed to find the types of sentence and phrase structures found in the narrative texts in English textbook. Based on the result of analysis, the data showed that every type of sentences occurred. The data also showed that not every phrase was occurred. Finally, it could be concluded that narrative texts consisted of every types of sentences and phrases to convey the meaning and story to the readers.